1985
DOI: 10.1128/jcm.22.5.861-862.1985
|View full text |Cite
|
Sign up to set email alerts
|

New germ tube induction medium for the identification of Candida albicans

Abstract: A new germ tube induction medium, composed of three parts Rabbit Coagulase Plasma with EDTA (BBl Mlicrobiology Systems) and two parts Tryp-Soy broth (Scott Laboratories, Inc.), was effective for the presumptive identification of Candida albica,is. This medium was safer to use, more accurate, and less expensive than other commercial germ tube induction media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…This classical method includes the incubation of a suspension of blastospores in human serum at 37°C for 2-3 h. 3 In several studies, the GTT in this format showed high sensitivities between 91% and 100%, and specificities of 95-100%. [5][6][7][8][9][10] However, the use of human serum for this test has several disadvantages: (i) the serum has to be fresh or deepfrozen; 3,4 (ii) the yeast inoculum has to contain <10 7 cells ml )1 , otherwise the germ tube production is inhibited; 4 (iii) the handling of pooled human sera includes the possible risk of infection with HIV or hepatitis virus; (iv) differences in performance between different batches of serum are likely. To avoid the necessity for extra safety precautions, other liquid media have been tested to replace human serum, like serum from different animals, tryptic soy broth (TSB) or peptone water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This classical method includes the incubation of a suspension of blastospores in human serum at 37°C for 2-3 h. 3 In several studies, the GTT in this format showed high sensitivities between 91% and 100%, and specificities of 95-100%. [5][6][7][8][9][10] However, the use of human serum for this test has several disadvantages: (i) the serum has to be fresh or deepfrozen; 3,4 (ii) the yeast inoculum has to contain <10 7 cells ml )1 , otherwise the germ tube production is inhibited; 4 (iii) the handling of pooled human sera includes the possible risk of infection with HIV or hepatitis virus; (iv) differences in performance between different batches of serum are likely. To avoid the necessity for extra safety precautions, other liquid media have been tested to replace human serum, like serum from different animals, tryptic soy broth (TSB) or peptone water.…”
Section: Discussionmentioning
confidence: 99%
“…2 The classical germ tube test (GTT) includes the incubation of a defined suspension of blastospores in human serum at 37°C for 2-3 h. 3,4 It showed a sensitivity between 91% and 100%, and a specificity of 95-100%. [5][6][7][8][9] As human serum needs to be fresh or frozen and the handling of pooled serum specimens causes safety problems, nonhuman serum and other liquid media were evaluated. However, these media often showed lower sensitivities ranging from 35% to 95%.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary identification was based on growth characteristics, colony morphology and cellular appearance. The ATB ID 32C assimilation test kit (BioMérieux, Marcy/Etoile, France) and the germ tube test (2) were used for further characterization.…”
Section: Phenotypingmentioning
confidence: 99%
“…The preparation of the ATB ID 32 C strips, the yeast suspension, and inoculation of the strips were carried out as recommended by the manufacturer. The strips were incubated at 30°C and the reactions were recorded after 24, 48 and 72 h. The germ tube formation test (Berardinelli & Opheim 1985) was used in the identification of C. albicans by incubating the cells at 37°C for 2 h in horse serum (Sigma, St. Louis, MO, USA); C. inconspicua was identified by the ATB ID 32 C test kit and by a growth test at 42°C for 12 h.…”
Section: Identification Of Yeasts and Bacteriamentioning
confidence: 99%